2023
DOI: 10.33235/wpr.31.1.40-48
|View full text |Cite
|
Sign up to set email alerts
|

What is the evidence that there is antimicrobial resistance associated with the use of topical antimicrobial preparations?

Abstract: Aims This review aimed to examine the effect of using topical antimicrobial preparations on antimicrobial resistance (AMR) by critically evaluating the currently available evidence.Method Using systematic review methodology, we considered original research studies employing a prospective design and written in English. The search was conducted in July 2022 using Ovid MEDLINE, Ovid EMBASE Medline and CINAHL databases. Data were extracted using a pre-designed extraction tool and all included studies were quality … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 38 publications
(106 reference statements)
0
1
0
Order By: Relevance
“…28 Choosing the right antiseptic for the patient is crucial to avoid causing unnecessary problems, including additional skin irritation. 32 Consistently, Blackburn et al 34 explored the effects of using topical antimicrobials on AMR and found that there was very limited evidence to prove efficacy, with most clinical evidence focusing on exploring the effectiveness of topical antimicrobials on infection and subsequent wound healing. The authors suggested that understanding the contribution of topical antimicrobials in AMR remains an important issue that is yet to be fully investigated.…”
Section: Ams and Antisepticsmentioning
confidence: 99%
“…28 Choosing the right antiseptic for the patient is crucial to avoid causing unnecessary problems, including additional skin irritation. 32 Consistently, Blackburn et al 34 explored the effects of using topical antimicrobials on AMR and found that there was very limited evidence to prove efficacy, with most clinical evidence focusing on exploring the effectiveness of topical antimicrobials on infection and subsequent wound healing. The authors suggested that understanding the contribution of topical antimicrobials in AMR remains an important issue that is yet to be fully investigated.…”
Section: Ams and Antisepticsmentioning
confidence: 99%